Qualitative and Quantitative Methods in Libraries Journal Special Issue - Brissett, Marilyn M.; Welsh, Teresa S. (Qualitative and Quantitative Methods in Libraries, 2019)
Since its inception, the International QQML conference has supported researchers whose focus is educational resources and on school libraries, culminating in the acceptance of a special session devoted exclusively to school library research at QQML 2015, Paris. This special issue of the QQML Journal includes selected papers related to school library research and related educational resources presented at QQML.